Gains from trade: The Costa Rican case - Alfaro Ureña, Alonso (2019)
One of the oldest and most interesting questions in the economic literature is how to quantify the gains from trade. Recently, Costinot & Rodríguez-Clare (2014) (CRC) developed a methodology that uses the World Input Output Database (WIOD) to compute this value for a list of countries. Costa Rica has never been part of this database given the lack of appropriate data. However, with the publication of a new Input Output Table for Costa Rica, the Foreign Trade Ministry (COMEX) was able to develop a domestic version of the WIOD that includes the country.  This paper presents the results of the CRC methodology using this version of the WIOD to compute gains from trade for the Costa Rican economy. Counterfactual exercises that compare the current situation with autarky and other average tariff levels using different productive structures and competition schemes in the economy are also presented. The results can provide valuable information on how much a small open economy like Costa Rica’s can benefit from international trade, and what are the differences in the results when compared to similar countries.